O que ensinam os professores de música na escola: um estudo no Sistema Municipal de Ensino de São Carlos - Prazeres, Flávia Costa (2018)
This research started with the question "What do music teachers from the Municipal System of Education (SME) teach in São Carlos?” It had, as general objective, the investigation on how music teachers select and organize contents for the initial years of basic education in the SME of São Carlos. As specific objectives, we seek to identify what content the teachers work with, analyze how these contents are organized, find out why they select these contents and why they consider them as musical knowledge valid to be taught in schools and, finally, to verify what purpose of teaching music they perform. In order to answer our research question, we carried out a bibliographical review, in search of works that relate Music Education and Curriculum. We define a focus on Content Selection and Organization, one of the dimensions of the curriculum, also using the typology of contentes presented by Antoní Zabala to accomplish the analysis. We use, as research method, a Study of Interviews and, as technique of data collection, the semi-structured interviews. Five effective music teachers from the SME of São Carlos participated in this research. We could observe, among the contents mentioned by teachers, the predominance of procedural contents. We were also able to analyze and understand three possibilities of content organization in the initial years of elementary school and to verify the purpose of music teaching in school, through the perspective of these teachers. Conclusively we verify that, in this Content Selection and Organization process, what looks like freedom, flexibility or protagonism to teach, is actually a false autonomy, forged in a context of instability of music in the school program and lack of official guidelines to music teaching.